When and how to replace the aortic root in type A aortic dissection - Leshnower, Bradley G.; Chen, Edward P. (Annals of Cardiothoracic Surgery, 2016)
Management of aortic root pathology during repair of acute type A aortic dissection (TAAD) requires a comprehensive evaluation of the patient’s anatomy, demographics, comorbidities and physiologic status at the time of emergent operative intervention. Surgical options include conservative repair of the root (CRR) (with or without replacement of the aortic valve), replacement of the native valve and aortic root using a composite valve-conduit and valve sparing root replacement (VSRR). The primary objective of this review is to provide data for surgeons to aid in their decision-making process regarding management of the aortic root during repair of TAAD. No time or language restrictions were imposed and references of the selected studies were checked for additional relevant citations. Multiple retrospective reviews have demonstrated equivalent operative mortality between aortic root repair and replacement during TAAD. There is a higher incidence of aortic root reintervention with aortic root repair compared to aortic root replacement (ARR). Experienced, high-volume aortic centers have demonstrated the safety of VSRR in young, hemodynamically stable patients presenting with TAAD. In conclusion, aortic root repair can safely be performed in the vast majority of patients with TAAD. Despite the increased surgical complexity, ARR does not increase operative mortality and improves the freedom from root reintervention. VSRR can be performed in highly selected populations of patients with TAAD with durable mid-term valve function.